New Settlements Policy in British Columbia - Bradbury, J. (Urban History Review / Revue d'histoire urbaine)

(untitled) (Urban History Review / Revue d'histoire urbaine, 1979)
Between 1965 and 1972 the provincial government of British Columbia introduced a new resource towns policy aimed at changing the relationship between corporations, the provincial government, and resource based settlements. The Instant Towns Act, together with the creation of new municipalities, represented a new level of government involvement and intervention in resource towns. The policy served to pass townsite costs from the companies to the workforce and to rationalise the further involvement of the state in resource extraction activities. The provincial government and the companies argued that a new settlements policy was necessary to replace the older model of company towns in order to attract a new and more stable labour force. At the same time as this policy was being shaped, the government was also engaged in developing industrial infrastructure to facilitate the expansion and the changing needs of capital. The Instant Towns Act of 1965 was part of the legislation for the expansion of large firms in the resource extraction sector. This form of infrastructure planning, to coincide with the changing structure of capital, reflects a level of state intervention in the economy of British Columbia, in other Canadian provinces, and indeed in most other western capitalist societies in recent years.